What Is a Summer Job Worth? The Impact of Summer Youth Employment on Academic Outcomes. (8th July 2014) - Leos‐Urbel, Jacob
Abstract This paper estimates the impact of New York City's Summer Youth Employment Program (SYEP) on school attendance and other educational outcomes in the following school year for a large sample of low‐income high school students. The program provides summer jobs and training to youth aged 14 to 21, and due to high demand allocates slots through a lottery. Analyses focusing on 36, 550 students who applied in 2007 indicate that SYEP produces small increases in attendance in the following school year, with larger increases for students who may be at greater educational risk: those aged 16 and older with low baseline school attendance. For this group, SYEP also increases the likelihood of attempting and passing statewide high school math and English examinations. Findings suggest that although SYEP's explicit goals focus on workforce readiness rather than academics, the program fosters engagement and success in school.